2012
DOI: 10.1037/a0027689
|View full text |Cite
|
Sign up to set email alerts
|

An examination of racial bias in the Beck Depression Inventory-II.

Abstract: Historically, many psychological measures were developed and standardized based on a primarily Caucasian population. These tests are subsequently applied to minorities and may be inappropriate and possibly even pathologizing. The widely used Beck Depression Inventory-II (BDI-II) was initially standardized on a sample of Caucasian university students and its use with minorities has only recently been investigated. This study examined the possibility of racial bias in the BDI-II by comparing Caucasian and Africa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…The applied study instruments were mainly self-developed and not validated. Many psychological instruments were developed and standardized based on a primarily Caucasian population and thus they were inappropriate to be applied to minority groups [87, 88]. Six of the studies [61, 63, 64, 66, 68, 72, 73] that were included in the final summary employed four validated instruments in total (Tables 1 to 4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The applied study instruments were mainly self-developed and not validated. Many psychological instruments were developed and standardized based on a primarily Caucasian population and thus they were inappropriate to be applied to minority groups [87, 88]. Six of the studies [61, 63, 64, 66, 68, 72, 73] that were included in the final summary employed four validated instruments in total (Tables 1 to 4).…”
Section: Discussionmentioning
confidence: 99%
“…Six of the studies [61, 63, 64, 66, 68, 72, 73] that were included in the final summary employed four validated instruments in total (Tables 1 to 4). Three instruments were successfully tested for cross-cultural validity, whereas the Beck Depression Inventory was tested among African-American and Caucasian students [88], the Job Content Questionnaire among Malay nurses [89], Iranian healthcare workers [90, 91] and hospital workers in Taiwan [92]. The same applies to the Nurses Work Index, which was validated for hospital nurses in South Korea [93] and Asian nurses working in the US [94].…”
Section: Discussionmentioning
confidence: 99%
“…Psychometric evaluations of the BDI-II have revealed that the test has high internal consistency (a ¼ .92) and adequate construct and factorial validity (Beck et al, 1996). Sashidharan, Pawlow, and Pettibone (2012) detected no racial biases in the BDI-II and added that the test is a valid measure of depressive symptoms among African Americans. Similarly, Grothe et al (2005) examined the reliability of the measure among low-income African Americans, which demonstrated high internal consistency (a ¼ .90) and yielded good item-total intercorrelations.…”
Section: Methodsmentioning
confidence: 98%
“…Questions about the efficacy of this measure have been raised by other researchers (Sashidharan et al, 2012). In their 2012 study, they examined whether the BDI-II contained racial bias.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…The BDI has been challenged regarding its appropriateness in use in African Americans since it was developed using primarily young white men and women in Canada (Beck, Steer, & Brown, 1996; Sashidharan, Pawlow, & Pettibone, 2012). The dangers of using a psychological instrument on subjects that it was not initially designed for are emphasized in another assessment measure.…”
Section: Introductionmentioning
confidence: 99%